Developing an institutional repository: implementation of DigiTool at Colorado State University Libraries - Zhou, Yongli, author; Liu, Shu, 1978-, author (Colorado State University. Libraries, 2008)
Presented at the Library and Information Technology Association (LITA) National Forum, October 17, 2008, Cincinnati, Ohio.
Keywords: metadata; Colorado State University Libraries; DigiTool; institutional repositories; digital repositories; customization